The Effectiveness of the Rahn Contract as a Restructuring of Murabahah Financing at BMT Kedinging Gresik Branch - Muftichatud Dzikroh; Dony Burhan Noor Hasan (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the effectiveness of the application of financing restructuring from a murabahah contract to a rahn contract at BMT Kedinding Surabaya Gresik Branch in order to mitigate the risk of Islamic financing. This research uses a qualitative approach with a case study design, where data is collected through interviews and observations. The findings show that the murabahah contract is one of the main instruments of Islamic financing that is widely used by members, especially traders, to support their business continuity. However, installment payment challenges often occur due to economic fluctuations and internal customer problems, thus increasing the risk of non-performing financing for BMT. To overcome this problem, BMT Kedinding implemented financing restructuring through a rahn contract. This step has proven effective in providing leeway to struggling customers while minimizing potential losses to the institution. The process of switching from a murabaha contract to a rahn contract is carried out without changing the agreed margin amount, giving customers more time to pay off arrears. This strategy is also in line with Sharia principles that prioritize flexibility and transparency in risk management. This study concludes that the application of the rahn contract as a form of financing restructuring can significantly reduce the risk of non-performing financing, while maintaining good relations between BMT and customers. These findings are expected to provide applicable recommendations for BMTs and other Islamic financial institutions in managing financing risk following Sharia principles. In addition, this research also emphasizes the importance of innovation and adaptation of Islamic financing products to answer the challenges faced by customers and financial institutions.